Navigating ethical challenges in the development and translation of biomaterials research - Hunckler, Michael D.; Levine, Aaron D. (Frontiers in Bioengineering and Biotechnology, 2022)
Biomaterials--from implanted iron teeth in the second century to intraocular lenses, artificial joints, and stents today--have long been used clinically. Today, biomaterials researchers and biomedical engineers are pushing beyond these inert synthetic alternatives and incorporating complex multifunctional materials to control biological interactions and direct physiological processes. These advances are leading to novel strategies for targeted drug delivery, drug screening, diagnostics and imaging, gene therapy, tissue regeneration, and cell transplantation. While the field has survived ethical transgressions in the past, the rapidly expanding scope of biomaterials science, combined with the accelerating clinical translation of this diverse field calls for urgent attention to the complex and challenging ethical dilemmas these advances pose. This perspective responds to this call, examining the intersection of research ethics -- the sets of rules, principles and norms guiding responsible scientific inquiry -- and ongoing advances in biomaterials. While acknowledging the inherent tensions between certain ethical norms and the pressures of the modern scientific and engineering enterprise, we argue that the biomaterials community needs to proactively address ethical issues in the field by, for example, updating or adding specificity to codes of ethics, modifying training programs to highlight the importance of ethical research practices, and partnering with funding agencies and journals to adopt policies prioritizing the ethical conduct of biomaterials research. Together these actions can strengthen and support biomaterials as its advances are increasingly commercialized and impacting the health care system.